Perinatal and early postnatal outcomes for fetuses with prenatally diagnosed d-transposition of the great arteries: a prospective cohort study assessing the effect of standardised prenatal consultation. (8th August 2017) - Qu, Yanji; Wen, Shusheng; Liu, Xiaoqing; Pan, Wei; Han, Fengzhen; Mai, Jinzhuang; Ou, Yanqiu; Nie, Zhiqiang; Gao, Xiangmin; Wu, Yong; Ohye, Richard G.; Chen, Jimei; et al.
Abstract: Background: The aim of this study was to explore perinatal and early postnatal outcomes in fetuses with prenatally diagnosed d -transposition of the great arteries and impacts of standardised prenatal consultation. Methods: All fetuses with prenatally diagnosed d -transposition of the great arteries prospectively enrolled at South China cardiac centre from 2011 to 2015. Standardised prenatal consultation was introduced in 2013 and comprehensive measures were implemented, such as establishing fetal CHD Outpatient Consultation Service, performing standard prenatal consultation according to specifications, and establishing a multidisciplinary team with senior specialists performing in-person consultations. Continuous follow-up investigation was conducted. Perinatal and postnatal outcomes were compared before and after consultation including live birth, elective termination of pregnancy, spontaneous fetal death, stillbirths, referral for surgery, and survival. Results: In all, 146 fetuses were enrolled with 41 (28%) lost to follow-up. Among 105 remaining fetuses, 29 (28%) were live births and 76 (72%) were terminated. After consultation, live birth rate was higher (50 versus 33%) and termination rate was lower (50 versus 76%), although there was no statistical significance. Excluding three live births without postnatal d -transposition of the great arteries, 65% (17/26) underwent arterial switch operation within 30 days. A total of three in-hospital deaths occurred and during the 10-month follow-up period, one death was observed. In one case, the switch procedure was performed at 13 months and the infant survived. Out of eight infants without arterial switch operation, two died. Conclusions: Live birth rate increased after consultation; however, termination remained high. Combining termination, patients without arterial switch operation, and operative mortality, outcomes of d -transposition of the great arteries infants can be improved. Standard consultation, multidisciplinary collaboration, and improved perinatal care are important to improve outcomes.